2020
DOI: 10.1021/acsomega.0c02582
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Ag–Sr-Substituted Hydroxyapatite/Chitosan Coatings Deposited via Electrophoretic Deposition: A Design of Experiment Study

Abstract: In this study, silver–strontium-doped hydroxyapatite (AgSr-HA)/chitosan composite coatings were deposited on a 316L stainless steel (SS) substrate via electrophoretic deposition (EPD). The Taguchi design of experiment (DoE) approach was used to optimize the EPD parameters such as the applied voltage, interelectrode spacing, and deposition time. Furthermore, the concentration of AgSr-HA particles in the suspension was also optimized via the DoE approach. DoE results demonstrated that the “homogeneous” coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 51 publications
(151 reference statements)
5
29
0
Order By: Relevance
“…Antibacterial results confirmed the strong antibacterial effect toward both Gram‐negative and Gram‐positive bacteria. Similar reports 22,29,44 illustrate the antibacterial effect associated with the chitosan and Ag. It was reported that 0.21 wt% Ag in the coating may lead to toxicity.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Antibacterial results confirmed the strong antibacterial effect toward both Gram‐negative and Gram‐positive bacteria. Similar reports 22,29,44 illustrate the antibacterial effect associated with the chitosan and Ag. It was reported that 0.21 wt% Ag in the coating may lead to toxicity.…”
Section: Resultssupporting
confidence: 74%
“…The 45S5 BG (Schott AG™, Germany) with an average particle size of 4 μm and nominal composition of 45 wt% SiO 2− , 24.5 wt% Na 2 O, 24.5 wt% CaO, 6 wt% P 2 O 5 28 was used. The PEEK powder (704 XF, Victrex™) with an average particle size of 10 μm was used to prepare PEEK/BG coatings 13,29,30 . The Ag and Mn‐doped MBGNs (Ag‐Mn MBGNs) were synthesized via modified Stöber method.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of Ag–Sr MBGNs was selected to be in the range of 1–5 g/L because the concentration lower than 1 g/L will not be enough to provide antibacterial effect and bioactivity. The concentrations higher than 5 g/L will cause the sedimentation of the dispersed Ag–Sr MBGNs 33 …”
Section: Methodsmentioning
confidence: 99%
“…The concentrations higher than 5 g/L will cause the sedimentation of the dispersed Ag-Sr MBGNs. 33 2.5 | EPD of C/G/Ag-Sr MBGNs 316L stainless steel (SS) foil was cut into dimensions of 2.5 cm × 3 cm. Samples were soaked in a mixture of ethanol and acetone and sonicated for 15 minutes followed by drying.…”
Section: Chitosan/gelatin Suspensionmentioning
confidence: 99%
See 1 more Smart Citation